Is adiponectin involved in morphea pathogenesis? – first observational study - Polańska, Adriana; Bratborska, Aleksandra Wiktoria; Kowalczyk, Michał J.; Żaba, Ryszard; Dańczak-Pazdrowska, Aleksandra (Frontiers in Immunology, 2025)
BackgroundMorphea is a chronic inflammatory condition characterized by fibrosis of the skin and/or subcutaneous tissues. Adiponectin is an adipokine known for its anti-inflammatory and antifibrotic properties. Lower levels of this protein have been associated with various diseases, but to date, no studies have evaluated adiponectin levels in patients with morphea.AimThe purpose of this study was to analyze the serum concentration of adiponectin in patients suffering from different types of morphea. Additionally, we aimed to investigate the relationship between adiponectin levels and clinical parameters, as well as the severity of skin involvement.MethodsThe study involved 67 patients with morphea and 30 healthy controls. Participants from the study group underwent a thorough clinical evaluation. Serum adiponectin levels were measured in both groups using enzyme-linked immunosorbent assay kits (ELISA).ResultsSerum adiponectin concentrations were significantly reduced in morphea patients compared to healthy controls. We observed no significant differences in adiponectin concentrations among the various morphea types; however, patients diagnosed with morphea en plaque (MEP) or generalized morphea (GM) had significantly lower serum adiponectin concentrations compared to healthy subjects. Furthermore, patients presenting with severe forms of the disease [the group included GM, deep morphea (DM), and linear morphea (LM)] had significantly reduced levels of adiponectin compared to healthy subjects. We found no significant differences in adiponectin levels between patients with active disease and patients in the non-active phase. There were no correlations between adiponectin levels and the localized scleroderma assessment tool (LoSCAT) score or disease duration.ConclusionPatients with morphea exhibit significantly lower levels of serum adiponectin, yet these levels do not correlate with the disease severity or activity. Further research is needed to explore the potential role of adiponectin in the pathogenesis of morphea.